Evaluation of the different sleep-disordered breathing patterns of the compressed tracheal sound. Issue 8 (August 2015) - Tenhunen, Mirja; Huupponen, Eero; Hasan, Joel; Heino, Otto; Himanen, Sari-Leena
Highlights Even if sustained partial obstruction is found to be common among sleep-disordered breathing (SDB) patients, it is not easily observed in conventional polysomnography recordings. Oesophageal pressure decreased and the tracheal sound presented most high frequency components in the 1001–2000 Hz frequency band during the sustained partial obstruction. The presented compressed tracheal sound analysis seems to provide an easy and reliable method for screening not only apneas or hypopneas but also sustained partial obstruction.